The Solution To Marriage Without A Marriage Certificate Based On Marriage Law And Islamic Law Is Associated With The Principle Of Legal Certainty - Putri, Rainaisty Puspa Kencana; Supriyatni, Renny; Nugroho, Bambang Daru (UNIVERSITAS PAKUAN, 2025)
Abstrak Penelitian ini membahas permasalahan perkawinan yang tidak dicatatkan di Indonesia, yang menyebabkan tidak adanya akta nikah dan dianggap sebagai perkawinan bawah tangan. Tujuan penelitian ini adalah menggambarkan solusi mengatasi perkawinan tanpa akta nikah berdasarkan Undang-Undang Nomor 1 tahun 1974 tentang Perkawinan dan Hukum Islam terkait Asas Kepastian Hukum. Metode penelitian yang digunakan adalah pendekatan yuridis normatif, dengan spesifikasi deskriptif-analitis melalui studi kepustakaan dan lapangan. Analisis data dilakukan secara kualitatif. Hasil penelitian menunjukkan bahwa solusi untuk mengatasi pernikahan tanpa akta nikah adalah dengan melakukan itsbat nikah yang memberikan kepastian hukum terhadap pernikahan tersebut. Namun, jika melanggar ketentuan Undang-Undang Perkawinan dan hukum Islam, perkawinan tersebut tidak bisa dilakukan itsbat nikah dan harus dilakukan pembatalan perkawinan. Pentingnya pencatatan nikah adalah memberikan legalitas identitas hukum kepada pasangan yang sah dan diakui oleh negara, sehingga mereka dapat memperoleh hak-hak administratif seperti kepastian hukum anak, pembuatan akta kelahiran, dan akibat hukum lainnya yang timbul dari perkawinan tersebut. Kata-Kata Kunci : Perkawinan, Undang-Undang Perkawinan, Hukum Islam. Abstract This research discusses the problem of marriages that are not registered in Indonesia, which results in the absence of a marriage certificate and it is considered an illegal marriage. The aim of this research is to describe a solution to overcome marriages without a marriage certificate based on Law Number 1 of 1974 concerning Marriage and Islamic Law related to the Principle of Legal Certainty. The research method used is a normative juridical approach, with descriptive-analytical specifications through literature and field studies. Data analysis was carried out qualitatively. The research results show that the solution to overcome marriages without a marriage certificate is to carry out a marriage itsbat which provides legal certainty for the marriage. However, if it violates the provisions of the Marriage Law and Islamic law, the marriage cannot be itsbat nikah and the marriage must be annulled. The importance of marriage registration is to provide legal identity to couples that is legal and recognized by the state, so that they can obtain administrative rights such as legal certainty of children, production of birth certificates, and other legal consequences arising from the marriage. Keywords: Marriage, Marriage Law, Islamic Law.